CRISPR-mediated rapid arming of poxvirus vectors enables facile generation of the novel immunotherapeutic STINGPOX - Jack T. Whelan; Jack T. Whelan; Ragunath Singaravelu; Ragunath Singaravelu; Ragunath Singaravelu; Fuan Wang; Fuan Wang; Adrian Pelin; Adrian Pelin; Levi A. Tamming; Levi A. Tamming; Giuseppe Pugliese; et al. (Frontiers in Immunology, 2023)
Poxvirus vectors represent versatile modalities for engineering novel vaccines and cancer immunotherapies. In addition to their oncolytic capacity and immunogenic influence, they can be readily engineered to express multiple large transgenes. However, the integration of multiple payloads into poxvirus genomes by traditional recombination-based approaches can be highly inefficient, time-consuming and cumbersome. Herein, we describe a simple, cost-effective approach to rapidly generate and purify a poxvirus vector with multiple transgenes. By utilizing a simple, modular CRISPR/Cas9 assisted-recombinant vaccinia virus engineering (CARVE) system, we demonstrate generation of a recombinant vaccinia virus expressing three distinct transgenes at three different loci in less than 1 week. We apply CARVE to rapidly generate a novel immunogenic vaccinia virus vector, which expresses a bacterial diadenylate cyclase. This novel vector, STINGPOX, produces cyclic di-AMP, a STING agonist, which drives IFN signaling critical to the anti-tumor immune response. We demonstrate that STINGPOX can drive IFN signaling in primary human cancer tissue explants. Using an immunocompetent murine colon cancer model, we demonstrate that intratumoral administration of STINGPOX in combination with checkpoint inhibitor, anti-PD1, promotes survival post-tumour challenge. These data demonstrate the utility of CRISPR/Cas9 in the rapid arming of poxvirus vectors with therapeutic payloads to create novel immunotherapies.